Learning styles and family satisfaction in a group of high and low performance students from a private university in Lima - Quezada Zevallos, Jenny (2019)
The present investigation is of a comparative descriptive type, with the objective of describing and comparing the learning style and the level of family satisfaction in a group of high and low performance students of a private university in Lima. The non-probabilistic sample, available sampling, made up of a total of 90 students, of which 28 have low academic performance and 62 high academic performance. The instruments used are: Katlen Buttler's Preference Inventory (Learning Styles) (1988) and the Family Satisfaction Scale for Adjectives. Barraca, J & Lópéz – Yarto, L. (2000). With respect to learning styles, the Sequential Abstract learning style is the one that is most developed in the entire sample studied and the Sequential Concrete learning style, in both groups they are concentrated at a Medium and High level, this learning style being the most preferred of the study group. The Total Family Satisfaction of both groups mostly presents a Low level (82.1% and 82.1% respectively).